O08.1 Assessing the Added Value of Internet Partner Services For Syphilis and HIV. (13th July 2013) - Bernstein, K T; Kohn, R; Wolf, W; Strona, F; Fann, C; Philip, S
Abstract : Background: Internet partner services (IPS) is the process of notifying named sexual partners to a newly diagnosed syphilis or HIV patient, where the only contact information for that partner is an email address or website handle. Although IPS is recommended by the Centers for Disease Control and Prevention, limited data are available regarding outcomes and the benefits to public health. San Francisco STD Prevention and Control Services has implemented IPS for over a decade. IPS data collected between 2006 and 2011 from newly diagnosed HIV and syphilis index patients and the outcomes of their partner investigations were examined. Methods: The proportion of partners with only internet contact information who, through IPS, had more contact information gathered was calculated. Additionally, the proportion of these partners who were presumptively treated or brought to treatment (for syphilis investigation) or who were tested for HIV (for HIV investigation) was also examined. Results: Between 2006 and 2011, 4, 255 partners were elicited from syphilis cases and 3, 607 partners from HIV cases. Of these partners, 645 from syphilis index cases and 691 from HIV index cases only had internet contact information. Overall, 47.1% and 46.6% of the syphilis and HIV internet partners, respectively, were successfully contacted and resulted in more contact information being gathered. Of the syphilis internet partners with updated contact information, 129 (42.4%) were either presumptively treated or brought to treatment and represented an increase of 7.2% in successful partner service outcomes. Among the HIV internet contacts, 55 (17.1%) were tested for HIV; a 7.9% increase in successful partner outcomes. Conclusions: By developing and maintaining IPS infrastructure in San Francisco, a substantially larger proportion of partners were able to be contacted by Disease Intervention Specialists (DIS) and successful outcomes of partner services increased for both syphilis and HIV.